Winging it - Lloyd, Megan Wagner (Graphix, an imprint of Scholastic, 2025)
Twelve-year-old Luna never wanted to move from California to Virginia, even if it is near historic Washington, DC, and no matter how excited her dad is to introduce her to the area where her late mother grew up. And she definitely doesn't want to live with a very formal grandmother she barely knows. But during a visit to the National Museum of Natural History, the rarely seen luna moth for which Luna was named sparks her curiosity. Using her mother's old naturalist notebooks as a guide, Luna, who has always preferred the indoors, endeavors to see a real luna moth with her own eyes. Learning more about nature just might help her make a new friend, figure out how to feel at home in her new life, and understand the mother she never got the chance to know. Megan Wagner Lloyd and Michelle Mee Nutter have again teamed up to tell a charming and funny story of family, friendship, adventure, and appreciating all life has to offer.